Developing an Electrostatic Discharge Machine to Determine the Resistance of Detonators used in Mining - M. Morales, Oswaldo (2016)
Investment in mining in Peru, to the year 2015, is in the order of 63,928 million. This activity is done mostly to over 3000 meters, where temperature and humidity are low, which favors the conservation of the generation of the electrostatic energy generated mainly by the triboelectric effect. This power generated, depending on its level, to download on detonators originates its on, causing damage to the miner, usually deadly type. To establish levels of electrostatic maximum energy of work an electrostatic machine has been developed to determine the resistance of detonators used in mining.